Tissue‐engineered vascular grafts for cardiovascular disease management: Current strategies, challenges, and future perspectives - Das, Kuntal Kumar; Tiwari, Ruchi Mishra; Shankar, Om; Maiti, Pralay; Dubey, Ashutosh Kumar (MedComm - Biomaterials and applications, 2024)
Cardiovascular diseases are the leading cause of mortality which primarily occurs due to the blood vessel obstruction or narrowing. Surgical procedures such as, coronary artery and peripheral artery bypass grafting frequently require vascular grafts for long‐term revascularization. However, using autogenous vessels, such as the internal thoracic artery and saphenous vein, especially for vessels with diameters less than 6 mm, are associated with number of concerns due to limited availability, invasive retrieval procedures, and aptness. To overcome these limitations, the development of tissue‐engineered vascular grafts (TEVGs) is in continuous thrust. This review comprehensively provides the potentiality of a range of artificial and naturally occurring biopolymers and their fabrication techniques, cell sources and seeding techniques to realize the state‐of‐the‐art TEVGs. Moreover, this review article presents a synopsis of insights obtained from a variety of in vitro and in vivo studies, including human clinical trials. It underscores the need for further exploration into key areas such as optimal cell sources, seeding techniques, mechanical properties, hemodynamics, graft integration, the impact of patient conditions, optimum burst pressure, sufficient suture strength, hydrophilicity, biodegradability, and related factors. In summary, the review offers insights into the current strategies, challenges, and future perspectives of TEVG. Design for nanofiberous graft based on PGA/PLCL: (A, B) Measuring dimensions and shape of thoracic inferior vena cava in sheep model using angiography. (C) CAD 3D‐printed mandrel for electrospinning. (D) Electrospinning the scaffold. (E, F) Implanting graft in sheep model. (G, H) SEM images of scaffold. (I) Intraoperative image of graft. Copyright permission from Fukunishi et al., 2017 [58].